1997
DOI: 10.1073/pnas.94.9.4267
|View full text |Cite
|
Sign up to set email alerts
|

DNA looping by Ku and the DNA-dependent protein kinase

Abstract: The DNA-dependent protein kinase (DNA-PK) is required for DNA double-strand break (DSB) repair and immunoglobulin gene rearrangement and may play a role in the regulation of transcription. The DNA-PK holoenzyme is composed of three polypeptide subunits: the DNA binding Ku70͞86 heterodimer and an Ϸ460-kDa catalytic subunit (DNA-PKcs). DNA-PK has been hypothesized to assemble at DNA DSBs and play structural as well as signal transduction roles in DSB repair. Recent advances in atomic force microscopy (AFM) have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
138
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(146 citation statements)
references
References 67 publications
5
138
1
Order By: Relevance
“…KU, DNA-PKcs, and XRCC4 all promote end-toend association of linear DNAs, both alone and in concert with each other (Cary et al, 1997;Pang et al, 1997;Yaneva et al, 1997;DeFazio et al, 2002). Such an association involves interaction between two molecules of KU (Cary et al, 1997) or DNA-PKcs (DeFazio et al, 2002), one on each DNA end.…”
Section: Structural and Biochemical Properties Of End-joining Proteinsmentioning
confidence: 99%
See 3 more Smart Citations
“…KU, DNA-PKcs, and XRCC4 all promote end-toend association of linear DNAs, both alone and in concert with each other (Cary et al, 1997;Pang et al, 1997;Yaneva et al, 1997;DeFazio et al, 2002). Such an association involves interaction between two molecules of KU (Cary et al, 1997) or DNA-PKcs (DeFazio et al, 2002), one on each DNA end.…”
Section: Structural and Biochemical Properties Of End-joining Proteinsmentioning
confidence: 99%
“…Although KU tends to cling to the DNA end, it can translocate into the interior, allowing multiple KU heterodimers to load onto longer DNA molecules (Mimori and Hardin, 1986;Paillard and Strauss, 1991;Cary et al, 1997;Pang et al, 1997;Yaneva et al, 1997). The end-bound KU occupies approximately 16-18 bp, as indicated by X-ray crystallography , DNase footprinting and ultraviolet crosslinking (Yoo and Dynan, 1999).…”
Section: Structural and Biochemical Properties Of End-joining Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourthly, we demonstrated that the cross-linked DNA-PK CS subunit retains its enzymic activity and is capable of phosphorylating itself as well as heterologous protein acceptors (Figure 3). Finally, the identification of DNA-PK CS bound to interior positions of DNA duplexes is not without precedent, as previous atomic force microscopy studies have shown trapping of the enzymic subunits both at the DNA ends and internally [37]. We noted, however, that this binding to internal positions of linear substrates is suppressed in the context of the nuclear protein environment ( Figure 7B).…”
Section: Discussionmentioning
confidence: 70%